PENGARUH PENDAPTAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA DAERAH - Fatimah, Nabiyatun Nur; Nopiyanti, Anita; Mintoyuwono, Danang (EQUITY, 2018)
This research is a quantitative research that aims to determine the effect of Local Government Revenue and Balancing Fund on Local Expenditure. This research uses data of Local Government Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund of Regency and City in East Java Province as sample. Selection of Regency and City is done randomly after determining acceptable sample amount that is 100% from all Regency and City in East Java Province. Hypothesis testing in research using Multiple Linear Regression Analysis with SPSS program and 5% significance level (0,05). The results of the test indicatethat the variable of Local Government Revenue and General Allocation Fund have significant influence to the Regional Expenditure. While the variable of Special Allocation Fund and Revenue Sharing Fund have an insignificant effect on Local Expenditure.